Detection of the thaumatin-like protein gene from Brassica rapa var. oleifera in honey with the Proofman-LMTIA method - Wei Yao; Dandan Xu; Dan Zhou; Jinxin Liu; Xiaohua Zhang; Yao Wang; Deguo Wang (CyTA - Journal of Food)
Honey adulteration has been on the rise with the increasing demand for high-quality honey. The ladders-shape melting temperature isothermal amplification (LMTIA) was a newly developed nucleic acid amplification technique, and the aim of this study was to establish a method combining the LMTIA with the proofreading enzyme-mediated probe cleavage (Proof-man probe) for detecting the thaumatin-like protein (TLP) genes of Brassica rapa var. oleifera in honey. The LMTIA primers was selected as a target to be designed, the temperature of the Proof-man LMTIA reaction was optimized, and the specificity, sensitivity, and applicability to the honey samples were determined. The results showed that the Proof-man LMTIA method was highly specific with a detection sensitivity of 30-40 copies genomic DNA/reaction at the optimal temperature of 60°C, and the amplification could be completed within 20 min. This method can detect the adulteration of low-price B. rapa honey into high-price honey.